The Effectiveness of Istinsyaq and Istinsar as an Islamic-Based Approach in the Prevention and Treatment of Sinusitis: Integration of Spiritual Values and Modern Medical Perspectives - Desi Widya Fitri; Ikhwan; Huda, Yasrul (NALAR FIQH: Jurnal Hukum Islam, 2024)
The mouth and nose are organs that are vulnerable to exposure to bacteria, viruses and germs, which can trigger various diseases including sinusitis. In Islam, the practices of istinsyaq and istinsar, which are part of ablution, have significant potential in cleansing the nasal cavity and preventing infections. Previous studies have shown the benefits of istinsyaq on respiratory health, but not many have linked it in depth to the prevention and treatment of sinusitis. This research uses the literature study method by analyzing data from various scientific sources such as Mendeley, Google Scholar, and Science Direct to explore the effectiveness of istinsyaq and istinsar in a medical and Islamic context. The results showed that the practices of istinsyaq and istinsar, when performed routinely five times a day in ablution, are similar in effectiveness to modern nasal irrigation methods, clearing mucus, dirt and microorganisms that can cause infection. The findings also indicate a reduced risk of respiratory tract infections and improvement in sinusitis symptoms. This study makes an important contribution by showing that Islamic teachings not only serve as a spiritual act of worship but also offer relevant practical solutions in public health. This study recommends further research to explore the application of istinsyaq as part of public health protocols in the prevention of respiratory diseases.